2018
DOI: 10.1111/cen.13762
|View full text |Cite
|
Sign up to set email alerts
|

The association between liver cirrhosis and fracture risk: A systematic review and meta‐analysis

Abstract: In conclusion, this study indicates that cirrhotic patients have an increased risk of fracture. Preventive measures should be instituted as early as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 23 publications
1
35
1
3
Order By: Relevance
“…Increased osteoporosis incidence is most commonly reported in cholestatic liver diseases, while less information is available regarding osteoporosis frequency in non‐cholestatic liver cirrhosis (Crawford, Kam, Donaghy, & McCaughan, 2003; Guañabens & Parés, 2018). Recent epidemiological data suggest that up to one‐third of non‐cholestatic liver cirrhosis patients, including alcoholic liver cirrhosis (ALC), are affected by osteoporosis (Ehnert et al, 2019; Liang et al, 2018). Furthermore, up‐to‐date studies in liver cirrhosis (LC) have emphasized that the lumbar spine is more likely affected than long bones (Crawford et al, 2003; Culafić et al, 2014), with a twofold vertebral fracture risk increase in LC patients (Liang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased osteoporosis incidence is most commonly reported in cholestatic liver diseases, while less information is available regarding osteoporosis frequency in non‐cholestatic liver cirrhosis (Crawford, Kam, Donaghy, & McCaughan, 2003; Guañabens & Parés, 2018). Recent epidemiological data suggest that up to one‐third of non‐cholestatic liver cirrhosis patients, including alcoholic liver cirrhosis (ALC), are affected by osteoporosis (Ehnert et al, 2019; Liang et al, 2018). Furthermore, up‐to‐date studies in liver cirrhosis (LC) have emphasized that the lumbar spine is more likely affected than long bones (Crawford et al, 2003; Culafić et al, 2014), with a twofold vertebral fracture risk increase in LC patients (Liang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological data suggest that up to one‐third of non‐cholestatic liver cirrhosis patients, including alcoholic liver cirrhosis (ALC), are affected by osteoporosis (Ehnert et al, 2019; Liang et al, 2018). Furthermore, up‐to‐date studies in liver cirrhosis (LC) have emphasized that the lumbar spine is more likely affected than long bones (Crawford et al, 2003; Culafić et al, 2014), with a twofold vertebral fracture risk increase in LC patients (Liang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ključne reči: osteoporoza, alkoholna ciroza jetre, fragilnost kostiju, prelom kosti, mineralna gustina kosti Većina istraživačkih grupa se slaže da je učestalost fraktura dva do tri puta veća kod pacijenata sa alkoholnom cirozom u poređenju sa zdravim kontrolnim individuama (18), mada su određene studije prijavile i osmostruko povećanje rizika od preloma kosti kod ovih bolesnika (17). Mnogi autori smatraju da je lumbalni deo kičmenog stuba češće osteoporotično izmenjen u poređenju sa ostalim mestima na skeletu.…”
Section: Sažetakunclassified
“…Pored toga, mortalitet nakon preloma kosti kod bolesnika sa ACJ je značajno nepovoljniji u odnosu na pacijente bez oboljenja jetre i pokazuje trostruko povećanje u poređenju sa zdravim pojedincima iste starosti (17). Uz prethodno navedeno, alkoholna ciroza je češće prisutna kod pacijenata muškog pola, kod kojih su koštane promene i osteoporoza manje učestale u poređenju sa ženskim osobama posle menopauze (18,22). Stoga nastanak osteoporoze i udružen povećan rizik od frakture kod ACJ pacijenata predstavlja značajno socijalno-ekonomsko opterećenje zdravstvenog sistema koje zahteva razvoj efikasnih mera prevencije, dijagnoze i lečenja.…”
Section: Sažetakunclassified
“…One of the most common triggers are infections, however, decompensation may also be triggered in the sequalae of other complications, eg bone fractures and subsequent immobilisation or surgery 3 . Recent studies suggested that patients with liver cirrhosis are per se at a higher risk for fractures when compared to patients without liver diseases 4‐6 . Given the economic burden for health care systems caused by bone fractures and the burden to patients, it is of pivotal importance to identify potential modifiable risk factors for the occurrence of fractures in high‐risk patient populations.…”
Section: Introductionmentioning
confidence: 99%